Auditoría clínica de la administración de fármacos en una residencia de personas mayores enfermas de Alzheimer y otras demencias neurodegenerativas Clinical audit regarding the administration of drugs in a residence for elderly people with Alzheimer's disease and other neurodegenerative dementias - Mar Prado Somalo; Amelia Cáceres Camblor; Nela Hernández Zorzano; Raquel Mendoza Quitanar; Noelia Ozaeta Alonso; Ibán Sáenz Abad; Vanesa López Sancho (Ediciones SPA S.L., 2006)
El equipo de enfermería de la Residencia El Sol observó cómo la administración de fármacos a los residentes conllevaba ciertos riesgos inherentes a la demencia. A partir de este hecho nos planteamos realizar una auditoría clínica para establecer qué tipo de incidencias se producía y determinar qué medidas tomar para minimizarlas. El estudio ha durado 12 meses y ha servido para identificar a los residentes con mayor riesgo, las incidencias de mayor frecuencia y buscar estrategias desde el equipo de enfermería que sean eficaces en la reducción del número de incidencias con la colaboración del resto del personal de la residencia. The Nursing Staff at the Residencia El Sol noticed there were significant risks associated to the administration of drugs to the residents given their condition of dementia sufferers. This was the starting point for a Clinical Audit whose aims are to determine what kind of incidents take place whilst administering medication and what measures can be implemented in order to minimize their incidence. The study lasted 12 months and has served different purposes such as identifying the residents at a highest risk, determining the most frequent incidents and helping the Nursing Team develop startegies with a view to reduce the number of those incidents in close collaboration with the rest of the staff at the Residencia El Sol.